Principales insectos plagas en el cultivo de melón (Cucumis melo L.) - Castro Gómez, Juan Carlos (2022)
Insect pests in the melon crop represent a very important problem from the nursery stage to harvest, causing a reduction in crop yield potential. Within the control of insect pests, biological control represents a fundamental basis for reducing insect populations to lower levels, without causing any damage to the ecosystem, considering natural enemies, thus being an effective alternative for the control of insect pests in the melon crop. Taking into account that there are also preventive control measures and cultural techniques that can be implemented for the control of insect pests in the melon crop. The information obtained was carried out through the technique of analysis, synthesis and summary, with the purpose of informing the reader about the main insect pests that attack the melon crop (Cucumis melo L.). From the above detailed, it was determined that the main insect pests that affect the melon crop are: Whiteflies (Bemisia tabaci and Bemisia argentifolii), Melon aphids (Aphis gossypii and Myzus persicae), Soldier worm complex (Spodoptera exigua Hüebner, Spodoptera albula Walker and Spodoptera frugiperda Smith), Melon maggot and fruit borer (Diaphania hyalinata Linnaeus and Diaphania nitidalis Stoll) and Leafminers (Liriomyza spp.). The most important and effective methods of control of insect pests in the melon crop are biological control through the application of predatory and parasitoid insects and entomopathogenic fungi, as well as preventive control by applying cultural techniques within the crop to reduce insect pest populations.